(untitled) (PRÁXIS EM SAÚDE, 2025)
Psychology professionals work in different professional contexts and deal daily with demands marked by trauma, mortality, psychological suffering, and intense emotions. Due to the empathetic and continuous nature of this work, these professionals are exposed to a specific form of suffering, referred to in the literature as compassion fatigue, a condition that can compromise the professional’s well-being and quality of life. This study aims to discuss compassion fatigue in psychologists working in clinical settings, based on a narrative review following the guidelines of the PRISMA model. Data collection was conducted in April 2025, using the PUBMED and LILACS databases, resulting in 57 articles. After screening and applying eligibility criteria, 4 studies were selected for analysis. The results indicate a predominance of qualitative research approaches, with recurrent use of semi-structured interviews. Participant recruitment was mostly conducted through social media and professional psychology networks. However, the analysis of the studies reveals a lack of theoretical cohesion, methodological weaknesses, small sample sizes, and results that, although relevant, superficially address the complexity inherent to clinical work in psychology.